Improving Seed Quality of Four Genotypes of Sweet Corn (Zea mays saccharata) Based on Harvest Time and Initial Water Content - Astryani Rosyad; Arya Widura Ritonga; Erik Mulyana; Punjung Medaraji Suwarno; Mertya Anugrah (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Quality seeds are crucial for successful sweet corn production. Various factors influence seed quality, including harvest time and initial water content. Therefore, understanding the interaction between harvest time and initial water content is essential for optimizing the quality of sweet corn seeds. This study aims to determine the optimal harvest time and initial water content for assessing the seed quality of four sweet corn genotypes: T13.1.8, SB13.1.3, T8.3.6, and T8.3.2. The experiment employed a factorial Randomized Complete Block Design (RCBD) with two factors. The first factor, harvest time, consisted of five levels (73, 76, 79, 82, and 85 days after planting [DAP]). In contrast, the second factor was the initial water content for seed testing, categorized as harvest water content and 10-12% moisture content. Each treatment was replicated three times, resulting in a total of 30 experimental units. The findings indicated that the sweet corn genotypes T13.1.8 and SB13.1, which were harvested at 76 to 82 hours after sowing (DAP) and had an initial water content of 10 to 12%, represented the optimal treatment combination. These genotypes exhibited germination rate and vigor index variables ranging from 92.7 - 100% and 70.67 - 96.67%. Sweet corn genotypes T8.3.6 and T8.3.2 can be harvested between 79 - 85 DAP with an initial water content of 10-12% to obtain seeds with a germination rate ranging from 86.00 - 98.67% and a vigor index of 58.00 - 86.67%. The study results can be used as a recommendation for seed producers to apply the harvest time and water content according to the genotype used, to ensure that the seeds produced have high viability and vigor.